Soil Bacterial Community Associated With High Potato Production and Minimal Water Use - Gumiere, Thiago; Gumiere, Silvio J.; Matteau, Jean-Pascal; Constant, Philippe; Létourneau, Guillaume; Rousseau, Alain N. (Frontiers in Environmental Science, 2019)
In agriculture, water consumption for crop production represents 69% of all water use. Precision irrigation systems based on available soil water have been developed to improve crop production, reducing water use. Besides the improvements in irrigation management, a better resolution of the optimal water level is required, and revealing the impact of soil matric potential on the soil microbial community may help. Here, the effect of four soil matric potential treatments (-15 kPa, -25 kPa, -30 kPa, and -45 kPa) was evaluated on the soil microbial community across three potato cultivars and two soil types (silt and sand). The results confirmed the soil matric potential with -25 kPa as the optimal irrigation level, which promoted high potato production using the minimal water use. The irrigation levels affected the composition, predicted functionality, and the ecological network of soil bacterial community. Water excess (-15 kPa) and deficit (-30 kPa, and -45 kPa) promoted an increase in microbial interaction and alpha-diversity. The results suggested higher Positive/Negative ratio for phyla Proteobacteria, Actinobacteria, and Acidobacteria in optimal irrigation level (-25 kPa) than other irrigation levels. Also, correlation analyses revealed an interesting association between the irrigation levels, potato production, and bacterial functionality, especially in the carbon cycle (fixation and emission). Therefore, this study proposed important associations between the soil bacterial community and water management, focusing on high potato production and minimal water use. The advancement of this knowledge may lead to a more comprehensive assessment of the optimal irrigation levels of others crop production systems. Furthermore, the inclusion of biological mechanisms, especially microbial interactions, in agriculture studies has the potential to contribute to the development of water management practices conducive to both increasing crop yield and maintaining a sustainable soil environment.